KEDUDUKAN LEMBAGA MEDIASI PERBANKAN SEBAGAI PILIHAN PENYELESAIAN SENGKETA ANTARA BANK DAN NASABAH PERBANKAN INDONES - Kadek Agus Sudiarawan (Universitas Pendidikan Nasional, 2018)
This research is aimed identifying the position of banking institutions as a choice of mediation dispute resolution between bank and customers banking of Indonesia as well as to find out the factors restricting and the cause of the weak level of the banking dispute resolution through mediation is associated with the introduction of PBI No. 8/5/PBI 2006 and PBI No. 10/1/PBI in 2008 about banking mediation.Types of research used in this paper included the normative legal research which put the law as a norm building system. This research uses secondary data where all of these data are analyzed using the qualitative methods. The report of this study is presented in a descriptive analysis. The results of the research indicated position of the institution of mediation as a form of banking is a real double protection for customers of banking Indonesia. As for restricting factors and causes of weak levels of dispute resolution through banking mediation include: yet the formation of independent banking mediation agencies banking, filing a dispute settlement arrangements are still concentrated in Bank Indonesia Jakarta, related publication duty setting the existence of institutions banking mediation without provisions supported sanctions, weak setting regarding the appointment and terms of the mediator, weak implementation arrangements and the peace agreement as well as the results of the pouring is not strictly speaking arrangements regarding sanctions against parties that do not comply with the mediation agreement banking.Keywords: Banking, Alternative Dispute Resolution, Bank Indonesia Regulation on Banking Mediation.